2004
DOI: 10.1016/j.jsg.2004.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bookshelf mechanisms using the mechanics of Cosserat generalized continua

Abstract: Bookshelf type mechanisms are commonly used to explain antithetic accommodation of deformations caused by direct shear. Stress analysis of such mechanisms have been proposed, mainly through the use of classic Mohr circle graphical constructions. The present work introduces an alternative framework for analysis, the mechanics of generalized Cosserat continua, although maintaining the same tools (Mohr circle construction). In this type of mechanics, kinematics of the material points incorporates independent rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The transpressive regime is a consequence of the nature of convergent triple junctions in the southern tips of Urals and northern tip of Southern Appalachians, which are connected by a transpressive transform through the European Variscides [ Arthaud and Matte , 1977]. Therefore the complete mechanical interpretation of domino style of distributed deformation must be addressed through generalized continua theory (such as Cosserat Continua [ Figueiredo et al , 2004]), or continuum micropolar theory [ Twiss and Moores , 1992]; both are more appropriate than classical continua theory to describe the schizosphere behavior [ Ribeiro , 2002] in presence of significant instability.…”
Section: Major Trends In Geodynamic Evolutionmentioning
confidence: 99%
“…The transpressive regime is a consequence of the nature of convergent triple junctions in the southern tips of Urals and northern tip of Southern Appalachians, which are connected by a transpressive transform through the European Variscides [ Arthaud and Matte , 1977]. Therefore the complete mechanical interpretation of domino style of distributed deformation must be addressed through generalized continua theory (such as Cosserat Continua [ Figueiredo et al , 2004]), or continuum micropolar theory [ Twiss and Moores , 1992]; both are more appropriate than classical continua theory to describe the schizosphere behavior [ Ribeiro , 2002] in presence of significant instability.…”
Section: Major Trends In Geodynamic Evolutionmentioning
confidence: 99%
“…As shown by Satake [33] and presented in more detail by other authors [10,19,13], the locus of the normal and shear components of the stress vector for all possible orientations is a (Mohr) circle whose centre does not lie on the axis of zero shear stress. This is shown in Figure 3, where it can be shown that AM = r, MC = q, OA = −p, so that the yield surface can be written as…”
Section: Two-dimensional Invariantsmentioning
confidence: 80%
“…The bookshelf model, proposed initially by Mandl [46], is the behavior of parallel faults that relate to a horizontal stack of books being displaced and consequently named 'bookshelf faulting' [46][47][48]. Mandl [46] described two basic modes of mechanism: the "dilational" mode and the "domino" mode.…”
Section: Discussionmentioning
confidence: 99%